Adults' Performance in an Episodic-Like Memory Task: The Role of Experience - Martin-Ordas, Gema; Atance, Cristina M. (Frontiers in Psychology, 2019)
Episodic memory is the ability to consciously recollect personal past events. This type of memory has been tested in non-human animals by using depletion paradigms that assess whether they can remember the “what,” “where” and “when” (i.e., how long ago) of a past event. An important limitation of these behavioral paradigms is that they do not clearly identify the cognitive mechanisms (e.g., episodic memory, semantic memory) that underlie task success. Testing adult humans in a depletion paradigm will help to shed light on this issue. In two experiments, we presented university undergraduates with a depletion paradigm which involved choosing one of two food snacks—a preferred but perishable food and a less preferred but non-perishable food- either after a short or a long interval. Whereas in Experiment 1, participants were asked to imagine the time between hiding the food items and choosing one of them; in Experiment 2 participants experienced the time elapsed between hiding the food items and choosing one of them. In addition, in Experiment 2 participants were presented with 2 trials which allowed us to investigate the role of previous experience in depletion paradigms. Results across both experiments showed that participants chose the preferred and perishable food (popsicle) after the short interval but did not choose the less preferred and non-perishable food (raisins) after the long interval. Crucially, in Experiment 2 experiencing the melted popsicle in Trial l improved participants’ performance in Trial 2. We discuss our results in the context of how previous experience affects performance in depletion tasks. We also argue that variations in performance on “episodic-like memory” tasks may be due to different definitions and assessment criteria of the “when” component.